Incubator humidity and temperature control in infants born at 22–23 weeks' gestation. (March 2022) - Kurimoto, Tomonori; Ibara, Satoshi; Ishihara, Chie; Naito, Yoshiki; Hirakawa, Eiji; Yamamoto, Tsuyoshi
Abstract: Background: Preterm infants, especially those born at ≤23 gestational weeks (GW), present with extremes in insensible water loss (IWL) and changes in water balance. Aims: To prevent water loss from the skin and achieve skin maturation without infection, we investigated transepidermal water loss (TEWL), IWL from the skin (IWL-s), and electrolyte balance with differences in high incubator humidity and temperature control from birth to postnatal 1 month in 22–23 GW and 24–25 GW infants. Study design: Prospective cohort study. Subjects: Extremely preterm infants born at 22–23 GW ( n = 11) and 24–25 GW (n = 11), admitted to the neonatal intensive care unit between September 2018 and October 2019. Outcome measures: Total fluid intake (TFI), fluid output volume, TEWL, IWL-s, and electrolyte balance were compared between the two groups with controlled incubator humidity and temperature, gradually decreasing the humidity and ambient temperature from 95% to 50% and from 37.0 to 34.0 °C, respectively, while maintaining the central body temperature at 36.5–37.5 °C. Results: TEWL and IWL-s between the 22–23 and 24–25 GW was not significantly different for infants at postnatal age. No significant difference in electrolyte imbalance was noted between the two groups, within the first 7 days. Differences in TEWL and IWL-s were eliminated with corresponding humidity and temperature adjustments. Conclusions: Incubator humidity and temperature control should aid management of 22–23 GW infants to reduce IWL, facilitate skin maturation, and prevent infection. Highlights: Optimized incubator settings eliminate water loss differences between 22 and 23- and 24–25-week gestation. Elimination of water loss occurs despite differences in skin maturation levels. Optimized incubator settings improve outcomes of extremely preterm neonates.